PRAKTIK KESIAPSIAGAAN DALAM MENGHADAPI BAHAYA KESELAMATAN DAN PENYAKIT SAAT BANJIR - Mahda, Mahda; Nurullita, Ulfa; Mifbakhuddin, Mifabkhuddin (Universitas Tarumanagara, 2024)
Flood disasters pose risks to safety and disease. Bandarharjo sub-district is an area prone to tidal flooding because it is located close to the coastline of Semarang City. In 2019, 3 residents suffered from Leptospirosis, of which 1 person died. The purpose of writing is to find out community preparedness practices for facing safety hazards and the dangers of disease due to floods. The method used is quantitative descriptive research using a cross sectional approach. The research subjects were 92 residents of RW 1, Bandarharjo Village, Semarang, who were interviewed using a questionnaire about their actions in dealing with safety and health hazards caused by flooding. All data was analyzed descriptively. The results of the research are that the education level of respondents who graduated from high school is 47.8%, the average length of stay in the location is 34 years, 34.78% of residents have preparedness practices for safety hazards during floods in the ready category, while 61.96% are classified as very ready in terms of preparedness practices. face the danger of disease during floods. 28.3% of respondents received sources of information via the internet, 31.5% of respondents had attended first aid outreach/training, 64.1% had attended scouting training, and 16.3% flood simulation training. Based on the analysis, the study's conclusion is that the preparedness practices of RW 1 residents of Bandarharjo Subdistrict to face safety hazards due to floods are included in the ready category, while the practices for facing the dangers of disease during floods are included in the very ready category. Keywords: Flood; Preparedness; Safety; Disease Abstrak Bencana banjir memberikan risiko pada keselamatan dan penyakit. Kelurahan Bandarharjo merupakan daerah rawan banjir rob karena berada pada posisi yang berdekatan dengan garis pantai Kota Semarang. Pada tahun 2019, 3 warga menderita Leptospirosis, di mana 1 orang di antaranya meninggal. Tujuan penulisan yaitu untuk mengetahui praktik kesiapsiagaan masyarakat menghadapi bahaya keselamatan dan bahaya penyakit akibat banjir. Metode yang digunakan adalah Penelitian deskriptif kuantitatif ini menggunakan pendekatan cross sectional. Subjek penelitian yaitu warga RW 1 Kelurahan Bandarharjo Semarang berjumlah 92 orang yang diwawancarai menggunakan kuesioner tentang tindakannya dalam menghadapi bahaya keselamatan dan kesehatan akibat banjir. Semua data dianalisis secara deskriptif. Hasil penelitian yaitu Tingkat pendidikan responden tamat SMA 47,8%, rata-rata lama tinggal di lokasi tersebut 34 tahun, 34.78% warga mempunyai praktik kesiapsiagaan terhadap bahaya keselamatan saat banjir dalam kategori siap, sedangkan 61,96% tergolong sangat siap dalam praktik kesiapsiagaan menghadapi bahaya penyakit saat banjir. 28.3% responden mendapatkan sumber informasi melalui internet, 31,5 % responden pernah mengikuti sosialisasi/pelatihan P3K, 64,1% pernah mengikuti pelatihan kepramukaan, dan pelatihan simulasi banjir 16,3%. Berdasarkan analisis, kesimpulan studi yaitu bahwa praktik kesiapsiagaan warga RW 1 Kelurahan Bandarharjo menghadapi bahaya keselamatan akibat banjir termasuk dalam kategori siap, sedangkan praktik menghadapi bahaya penyakit saat banjir termasuk dalam kategori sangat siap.